Simple and Approximately Optimal Contracts for Payment for Ecosystem Services - Li, Wanyi Dai; Ashlagi, Itai; Lo, Irene (Management Science, 2023)
Many countries have adopted payment for ecosystem services (PES) programs to reduce deforestation. Empirical evaluations find such programs, which pay forest owners to conserve forest, can lead to anywhere from no impact to a 50% reduction in deforestation level. To better understand the potential effectiveness of PES contracts, we use a principal–agent model, in which the agent has an observable amount of initial forest land and a privately known baseline conservation level. Commonly used conditional contracts perform well when the environmental value of forest is sufficiently high or sufficiently low, but can do arbitrarily poorly compared with the optimal contract for intermediate values. We identify a linear contract with a distribution-free per-unit price that guarantees at least half of the optimal contract payoff. A numerical study using U.S. land use data supports our findings and illustrates when linear or conditional contracts are likely to be more effective. This paper was This paper was accepted by Beril Toktay, Special Section of Management Science on Business and Climate Change. Funding: W. Dai Li was supported by a Stanford Interdisciplinary Graduate Fellowship. I. Lo was supported by an Environmental Venture Project Grant from the Stanford Woods Institute for the Environment. Supplemental Material: Data and the e-companion are available at https://doi.org/10.1287/mnsc.2021.4273 .